An over-damped multimodal adaptive nonlinear static analysis for seismic assessment of infilled RC buildings. (15th February 2021) - Barbagallo, Francesca; Bosco, Melina; Ghersi, Aurelio; Marino, Edoardo M.
Highlights: This analysis is based on a multimodal adaptive approach. The proposed analysis includes a direct evaluation of the displacement demand. An overdamping correction is proposed to consider the structural energy dissipation. A new damping law is calibrated for RC-frames considering the effect of infills. The efficacy of the proposed analysis and other literature approaches are examined. Abstract: In the world, many existing buildings with RC framed structure are extremely vulnerable, as they were designed to sustain gravity loads only, or to resist seismic actions lower than those expected today. Since a complete renewal of the existing building heritage is not possible, the seismic assessment of existing structures has gained importance in recent years to identify the structural deficiencies and design the most appropriate retrofit interventions. This paper proposes a multimodal adaptive nonlinear static method of analysis named overDamped Displacement Adaptive Procedure (D-DAP). This method has been developed from the combination of the approaches adopted by Pinho et al. and Lenza et al. In addition, the D-DAP explicitly considers the increase of the energy dissipation due the cumulated damage in the structure by updating the value of equivalent viscous damping ratio according to a new damping law properly calibrated for RC frames with and without infill panels.